An Electric Model of Cracked Solar Cells Accounting for Distributed Damage Caused by Crack Interaction. (August 2016) - Paggi, Marco; Berardone, Irene; Martire, Marco
Abstract: Electric models based on a distributed series resistance along the grid line can be used to predict the current through the thickness of the Silicon solar cell, as well as the current and the voltage along the grid line. In the presence of a crack intersecting a finger, a localized electrical resistance dependent on the crack opening has to be introduced in that intersection point. In the present study, a refinement of these electric models is proposed by introducing a sheet resistance dependent on the amount of damage induced by cracks in the surrounding material. The proposed model is successfully validated in reference to experimental data on mono-crystalline Silicon solar cells with cracks artificially created by Vickers indentation, providing an insight into the electric degradation mechanisms caused by crack interaction phenomena.